Дорнод Монголын нүүрсний цацраг идэвхийг судалсан дүн - Н, Норов; О, Отгонсүрэн; С, Даваа (Scientific transaction of the National University of Mongolia. Physics, 2022)
The study of Radioactivity of the brown coals using gamma Spectrometer is been discussed. The samples from the coal mines of Eastern Mongolia: Aduunchuuluun, Baga Nuur, Bumbat and Tal Bulag were analyzed, and the natural radionuclides content ranges from 2.5 to 4340 Bq/kg for Ra- 226, from 1.5 to 46 Bq/kg for Th-232; and from 1.4 to 360 Bq/kg for K-40 in various coal mines.